2022
DOI: 10.3390/genes13101888
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and Proteomic Biomarkers of Elevated Alcohol Use Predict Epigenetic Aging and Cell-Type variation Better Than Self-Report

Abstract: Excessive alcohol consumption (EAC) has a generally accepted effect on morbidity and mortality, outcomes thought to be reflected in measures of epigenetic aging (EA). As the association of self-reported EAC with EA has not been consistent with these expectations, underscoring the need for readily employable non-self-report tools for accurately assessing and monitoring the contribution of EAC to accelerated EA, newly developed alcohol consumption DNA methylation indices, such as the Alcohol T Score (ATS) and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Measurement issues have often made direct assessment of health impacts, health behaviors, and pro-inflammatory processes difficult, and have forced researchers to rely on self-reported health and behavior. Recently, there have been developments in the use of methylation markers that allow more direct assessment in each of these domains, allowing researchers to bypass self-report [ 22 , 23 ]. In addition, epigenetic measurement has the potential to help examine mechanisms of effect.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement issues have often made direct assessment of health impacts, health behaviors, and pro-inflammatory processes difficult, and have forced researchers to rely on self-reported health and behavior. Recently, there have been developments in the use of methylation markers that allow more direct assessment in each of these domains, allowing researchers to bypass self-report [ 22 , 23 ]. In addition, epigenetic measurement has the potential to help examine mechanisms of effect.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in our clinical experience (BP, AA, and RP), we have found that patients often misrepresent their alcohol use history. Although others may disagree, in our research experience, we standardly employ multiple biomarkers of alcohol consumption including the CDT and epigenetic biomarkers to assess alcohol use in our subjects and routinely find much stronger relationships between biomarkers of alcohol use to one another and to key outcomes than to those found with self-report [ 10 , 12 , 45 ]. When considering the circumstances in which most of the subjects in this study were presented, this is certainly understandable.…”
Section: Discussionmentioning
confidence: 99%
“…ATS levels and MSdPCR assessment of cg07375256 levels were conducted using reagents and software from Behavioral Diagnostics (Coralville, IA) and from Bio-Rad (Hercules, CA) using our previously published methods [ 9 , 10 , 12 , 37 ]. Similarly, the smoking intensity at cg05575921, a generally accepted biomarker for smoking intensity [ 38 ], was assessed using reagents and software from Behavioral Diagnostics (Coralville, IA) and from Bio-Rad (Hercules, CA) according to our previously described methods [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation